3-Dimensional Blood Clot Simulation On Plastic Arterial Catheter using GAMBIT & FLUENT - Afzal Reza Bin Ali Rahman, Afzal Reza (Universiti Teknologi Petronas, 2011)
The Volume Of Fluid (VOF) model is a surface-tracking technique applied to a fixed Eulerian mesh. It is designed for two or more immiscible fluids where the position of the interface between the fluids is of interest. The fluids share a single set of momentum equations, and the volume fraction of each of the fluids in each computational cell is tracked throughout the domain. As such, VOF is an advection scheme that acts as a numerical recipe that allows the programmer to track the shape and position of the interface, but it is not a standalone flow-solving algorithm. The Navier Stokes equations describing the motion of the flow have to be solved separately. The movement of one fluid with regards to its interface is studied to help the researchers and engineers in deciding certain parameters such as pressure and velocity in plastic arterial catheter in order to reduce error, computational cost, and save simulation time. Good resemblance between CFD predictions with the experimental data in certain locations was obtained with the factor of species (blood clot) transport and pressure profile, where dependence of VOF models and grid sizes were discussed in details. The results show us that, the demand in grid study is vital to obtain accurate results with minimal computational cost. On the other hand, wall adhesion is solved in an iterative way, modifying holdups at the wall until the specified wall contact angle had been satisfied. Since the VOF method is a Direct Numerical Simulation (DNS) approach, the time and length scales on which the equations are being solved should be sufficiently small to directly take fluctuating fluid motion due to turbulence into account. Therefore, VOF simulations do not incorporate any other turbulence models, thus only applicable to laminar models.